Doping, the inspection game, and bayesian enforcement - Kirstein, R. (Journal of Sports Economics, 2014)
"Bayesian enforcement" assumes that doping tests are imperfect. Moreover, the enforcer is interested in fostering compliant behavior and making correct decisions. Three types of perfect Bayesian equilibria exist, which differ in their punishment styles: "tyrannic," "draconian," and "lenient." The equilibrium probability of compliant behavior is highest in the lenient equilibrium; therefore, the legal framework of the enforcement should aim at unselecting the draconian and tyrannic equilibria. Total deterrence is impossible as long as the signal is imperfect. An increase in punishment would not increase the probability of compliant behavior.